Branch and Bound algorithm for solving the total weighted tardiness criterion for the permutation flowshop scheduling problem with time lags - Almathkour, Fatmah Bader; Belgacem, Omar; Toumi, Said; Jarboui, Bassem (Yugoslav Journal of Operations Research; Vol 32 No 1 (2022), 2022)
This paper deals with the permutation flowshop scheduling problem with time lags constraints to minimize the total weighted tardiness criterion by using the Branch and Bound algorithm. A new lower bound was developed for the flowshop scheduling problem. The computational experiments indicate that the proposed algorithm provides good solution in terms of quality and time requirements.